An Analysis of the Effectiveness of the Human Resource Arrangements within the Ghanaian Decentralized Government System: Views of Staff of Cape Coast Metropolitan Assembly - Odoom, Daniel (International Journal of Applied Research, 2019)
Adequate human resource (HR) is critical in ensuring goal attainment within the broader framework of local government systems. Like any other institutions, the District Assemblies (DAs) which are central to the success of local government systems in Ghana require adequate and well-qualified personnel in order to be able to perform the responsibilities entrusted to them. However, it is believed that many DAs in Ghana lack the requisite HR for the performance of their mandated functions. This poses a serious danger to the viability of Ghana’s decentralized government system. Against this backdrop, this study sought to examine the views of employees of DAs on the HR arrangements within the country’s decentralized government system using Cape Coast Metropolitan Assembly as a case. The study was descriptive and exploratory, with the Coordinating Director, Deputy Directors, Sectional Heads, and other members of the Central Administration as the population. Purposive and stratified sampling methods were used to select 54 respondents for the study, with interview schedule and interview guide as the research instruments. Frequencies, percentages, Mann Whitney U test and content analyses were employed for the study. The study found that the existing institutional framework contributes to the problems the Assembly faces regarding its HR capacity. Also, the Assembly did not have adequate and well-qualified personnel to carry out its mandate. Again, factors such as low salaries, poor recruitment and selection policy, ineffective staff replacement and transfer policy, low motivation and inadequate training and development hampered the HR capacity at the Assembly. It was found that no differences exist in the opinions of males and females with respect to the factors affecting the Assembly’s HR capacity. It is recommended that the Ministry of Local Government and Rural Development (MLGRD) should re-examine its HR policies in order to grant autonomy to the various Personnel Management Departments in the District Assemblies. This will improve the HR situation at the Assembly since it will reduce excessive delays and travelling costs involved in addressing the HR challenges in the DAs.
Research Article
Keywords: Effectiveness, Human Resource Arrangements, Ghanaian, Decentralized Government System, Cape Coast Metropolitan Assembly; Human Resource, Ghanaian Decentralized, Government System, Cape Coast Metropolitan Assembly